QT Prolongation in Critically Ill Patients With SARS-CoV-2 Infection. (7th January 2022) - El Nekidy, Wasim S.; Almuti, Khalid; ElRefaei, Hazem; Atallah, Bassam; Mohammad, Lana M.; AlMahmeed, Wael; Badr, Mohamed; Abdallah, Khaled; Hamed, Fadi; Mallat, Jihad
Background: Several reports linked the use of repurposed drugs such as hydroxychloroquine (HCQ), azithromycin, lopinavir/ritonavir, and favipiravir with QT interval prolongation in patients with SARS-CoV2 infection. Little is known about the risk factors for QT interval prolongation in this population. We sought to describe the prevalence and identify the main risk factors associated with clinically significant corrected QT (QTc) prolongation in this population. Methods: We conducted a retrospective analysis of critically ill patients who were admitted to our intensive care unit (ICU), had at least one electrocardiogram performed during their ICU stay, and tested positive for SARs-CoV-2. Clinically significant QTc interval prolongation was defined as QTc >500 milliseconds (ms). Results: Out of the 111 critically ill patients with SARS-CoV-2 infection, QTc was significantly prolonged in 47 cases (42.3%). Patients with a clinically significant QTc prolongation had significantly higher proportions of history of cardiac diseases/surgery (22 [46.8%] vs. 10 [15.6%], P < .001), hypokalemia (10 [21.3] vs. 5 [7.8%], P = .04), and male gender (95% vs. 82.8%, P = .036) than patients with QTc ≤500 ms, respectively. A total of 46 patients (41.4%) received HCQ, 28 (25.2%) received lopinavir/ritonavir, and 5 (4.5%) received azithromycin. Multivariate logistic regression analysis showed that a history of cardiac disease was the only independent factor associated with clinically significant QTc prolongation ( P = .004 for the likelihood-ratio test). Conclusion: The prevalence of clinically significant QTc prolongation in critically ill patients with SARS-CoV-2 infection was high and independent of drugs used. Larger prospective observational studies are warranted to elucidate independent risk factors associated with clinically significant QTc prolongation in this study population.